FRI0290 EFFICACY AND SAFETY OF TOCILIZUMAB IN PATIENTS WITH GIANT CELL ARTERITIS AND VISUAL DISTURBANCES. (June 2019) - Rubbert-Roth, Andrea; Tschuppert, Scott; Neumann, Thomas; Benecke, Ulf; Pirker, Ian; Kempis, Johannes von
Abstract : Background: Giant cell arteritis (GCA) affects cranial arteries and, as a complication, may lead to visual disturbances and ultimately blindness. Tocilizumab (TCZ) has recently been approved for treatment of GCA. Data on its efficacy and safety in patients who present with visual affection are limited. Objectives: To study the outcome of patients with GCA and visual affection treated with TCZ. Methods: We performed this retrospective single center study of all patients with GCA and visual disturbances consecutively seen in our clinic between April 2013 and January 2019 who underwent treatment with tocilizumab in addition to glucocorticosteroids (GC). Results: 16 GCA patients (13 women, 3 male) with a mean age of 76.3 ± 9.7 yrs at GCA diagnosis and 25 affected eyes were treated with tocilizumab in addition to GC. 2/16 patients presented with visual disturbances under treatment with under prednisone, and 1/16 patient under leflunomide for polymyalgia. 2 patients experienced unilateral blindness while receiving iv pulse GC. AAION was diagnosed in 20/25 eyes, PION in 1/25 eyes and occlusion of the central retinal artery in 4/25 eyes. Loss of vision below 10% occurred in 12/25 eyes. None of the patients had bilateral blindness at baseline. 5/25 eyes were affected by hemi- or sectorial anopsia, blurred vision was reported in 8/25 eyes. 14 patients were treated with TCZ iv 8mg/kg every 4 weeks, 2 patients received sc TCZ at 162mg every 2 weeks. All patients with visual symptoms received intravenous GC boluses, followed by prednisone 1mg/kg/day with subsequent stepwise reduction. Concomitant treatment consisted of low dose ASS in 11/16 and anticoagulants/NOAKs in 5/16 patients. Statins were used in 9/16 patients. Mean disease duration before initiation of tocilizumab was 3.8 + 5.7 months. 13/16 patients started with TCZ within 2 months after diagnosis of GCA, in 3 patients TCZ was started because of refractory and/or relapsed disease. Mean duration of TCZ therapy was 14.8 ± 9.4 months. 9/16 patients were able to stop GC after a mean duration of 14.8 ± 9.5 months and have been steroid-free for an average time of 14.7 ± 10 months (as of January 2019). 4/7 patients with a disease duration of less than 6 months are still on a GC taper at present. In addition to cessation of GC, 4 patients have discontinued TCZ and are drug-free at present for 4, 9, 31 and 35 months, respectively. In 2 additional patients, TCZ dose was decreased and/or the dosing interval extended. None of the 12 eyes with vision < 10% have recovered, but no new vision disturbances occurred during TCZ or after cessation of either TCZ/or GC. Overall, TCZ was well tolerated with no major side effects. 22 patients experienced vascular complications (stroke, development of an aortic aneurysm) during treatment with TCZ. Conclusion: Although TCZ was unable to reverse unilateral blindness, no new visual symptoms occurred during or after TCZ treatment and the majority of patients were able to stop or reduce GC. Disclosure of Interests: Andrea Rubbert-Roth Consultant for: Chugai, Eli Lilly, Roche, and Sanofi, Speakers bureau: AbbVie, Bristol-Myers Squibb, Chugai, Hexal/Novartis, Janssen, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, and Sanofi, Scott Tschuppert: None declared, Thomas Neumann: None declared, Ulf Benecke: None declared, Ian Pirker: None declared, Johannes von Kempis Consultant for: Pfizer, UCB, Lilly, Sanofi.